066 Vasodilatory capacity at peak exercise in treated heart failure patients are not diminished. (22nd September 2015) - Lewis, N T; Barker, Diane; Schlosshan, D; Patwala, A; Goldspink, D F; Tan, L B
Abstract : Background: Previous received dogma has propagated the concept that heart failure (HF) patients have compromised vasodilatory capacity during exercise through various vascular mechanisms, thereby reducing their exercise capacity through peripheral (vascular) factors rather than central (cardiac) factors. We tested whether such a concept is still valid in modern HF patients receiving current standard HF therapies. Methods and Results: We recruited 150 female participants (133 normal healthy controls, age 48.5±13.1 (SD) years; 17 DCM patients, age 41.5±14.2 years) with no known coronary or other vascular diseases, and compared their central haemodynamic responses during volitional maximal exercise. The exercise capacity of controls spanned the same ranges as those of the HF patients. All patients performed symptom-limited cardiopulmonary exercise testing (CPX) with breath-by-breath analyses of respiratory gases and non-invasive haemodynamic measurements employing standard auscultatory sphygmomanometric and rebreathing methods. The patients performed a total of 30 CPX's. The peak O2 consumption spanned from 1.20 to 2.45 L/min in DCM patients and from 1.15 to 2.44 L/min in controls. As shown in the figure, at peak exercise the systemic vascular resistances (SVR) of DCM patients were lower (532±154 dyn.s.cm-5) than those of controls (654±118 dyn.s.cm-5). Conclusion: With modern HF therapy, the lower peak exercise SVR in HF patients compared to normal healthy controls demonstrates that there is no evidence of compromised systemic vasodilatory capacities in HF patients. The long-held dogma of vasodilatory incapacity in HF propagated >3 decades ago is no longer valid nowadays.